A new approach method for characterizing inter-species toxicodynamic variability. Issue 24 (17th December 2021) - Burnett, Sarah D.; Karmakar, Moumita; Murphy, William J.; Chiu, Weihsueh A.; Rusyn, Ivan
ABSTRACT: Inter-species differences in toxicodynamics are often a critical source of uncertainty in safety evaluations and typically dealt with using default adjustment factors. In vitro studies that use cells from different species demonstrated some success for estimating the relationships between life span and/or body weight and sensitivity to cytotoxicity; however, no apparent investigation evaluated the utility of these models for risk assessment. It was hypothesized that an in vitro model using dermal fibroblasts derived from diverse species and individuals might be utilized to inform the extent of inter-species and inter-individual variability in toxicodynamics. To test this hypothesis and characterize both inter-species and inter-individual variability in cytotoxicity, concentration-response cytotoxicity screening of 40 chemicals in primary dermal fibroblasts from 68 individuals of 54 diverse species was conducted. Chemicals examined included drugs, environmental pollutants, and food/flavor/fragrance agents; most of these were previously assessed either in vivo or in vitro for inter-species or inter-individual variation. Species included humans, the typical preclinical species and representatives from other orders of mammals and birds. Data demonstrated that both inter-species and inter-individual components of variability contribute to the observed differences in sensitivity to cell death. Further, it was found that the magnitude of the observed inter-species and inter-individual differences was chemical-dependent. This study contributes to the paradigm shift in risk assessment from reliance on in vivo toxicity testing to higher-throughput in vitro or alternative approaches, extending the strategy to replace use of default adjustment factors with experimental characterization of toxicodynamic inter-individual variability and to also address toxicodynamic inter-species variability.